Factors affecting student comprehension in EMI classrooms: Teachers’ perceptions - Nurymbetov, Yedil; Shabdenov, Aizhan; Abduldayev, Yerkhan; Nogaibayeva, Akmarzhan; Bakic-Miric, Natasa; Kassymova, Gulzhaina (Jurnal Cakrawala Pendidikan, 2025)
English-medium instruction (EMI) has become popular in educational settings worldwide and has attracted scholars’ attention, prompting them to investigate factors influencing student comprehension in EMI classrooms. This paper identifies the factors influencing students' use of English in EMI classrooms, which has become a significant issue within the field. The study's data were collected based on the results of interviews with English language teachers in Astana, and a thematic analysis was performed. It was determined that task comprehension, the teacher's level of English skills, and comprehension of terminology and lessons affect the students' English language comprehension according to teachers' perceptions. It was found that the identified factors can have both positive and negative effects. This study aligns with broader issues on the internationalization of higher education and the growing prevalence of English as a global language. It synthesizes research findings to identify key factors influencing student understanding in EMI classrooms from the teachers' perspective, providing key insights and recommendations for further research.